Effect of sertraline and fluoxetine on the reproductive abilities of male rats Rattus norvegicus - Subhi Madlool, Zaman; Abood Faris, Satar; M. Hussein, Ali (University of Thi-Qar Journal of Science, 2019)
The present study was designed to know the effect of sertraline and fluoxetine on the reproductive abilities of male rats. The experiment consisted of five groups (each group contains of 5 males), the first (control) group was injected (I.P) with 0.25ml of normal saline, the second group was injected with sertraline (10 mg / kg), the third group was injected with sertraline (20 mg / kg), the fourth group was injected with fluoxetine (5 mg / kg) and the fifth group was injected with fluoxetine (10 mg / kg). .The results showed a significant decrease (P≤0.05) in the number of sperms and in the level of testosterone hormone and a significant increase (P≤0.05) in the percentage of sperm deformities in all treated groups when compared with control group. The histologically examination showed that there was changes in the testis including the dissociation of the connective tissue in second and fifth groups, decrease in the number of spermatgonia, and Leydig cells, bloody congestion in third and fifth groups, hemorrhage and necrosis in forth group.